Judgmental the Identity of New York Times between Al Jazeera on Indonesia General Election: Appraisal Framework - Hanief, Ibnu Hudzaifah; Khaidir, Nor Shahira Binti (JSSH (Jurnal Sains Sosial dan Humaniora), 2024)
This study aims to identify the terminology Al Jazeera and the New York Times used in their news reports on the 2024 Indonesian General Election, which had many candidates. In particular, this article identifies the data gathered from the appraisal system's components of attitude judgment (Martin & White, 2005), described in interpersonal (Martin & Rose, 2007). The number of negative judgments is much higher than the number of positive judgments. Out of the 21 total data, 76.2% are identified as negative judgments with 16 data, while the remaining 23.8% are positive judgments with 5 data. Once the analysis is carried out thoroughly, it is found that 80.9% of the data is categorized under social esteem, and the other 19.1% falls under social sanction. There are indications that the disparity between the positive and negative judgments is because of the controversy that preceded and followed the 2024 Indonesian General Election, in which Gibran, the President’s son, nominated Prabowo as a candidate and won the general election. This study's language assessment (appraisal) tries to identify two forms of judgment in four online international newspaper segments.